Literasi Navigasi Digital: Memanfaatkan Google Maps Untuk Meningkatkan Visibilitas UMKM Desa Banyubiru: Pengabdian - Dyah Maya Nihayah; Agus Hermanto; Prasetyo Ari Bowo; Annis Nurfitriana Nihayah; Jeane Talakua; Fredericho Mego Sundoro; Putri Patria Kusuma (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The knowledge of Micro, Small, and Medium Enterprises (MSMEs) in Banyubiru Village in utilizing digital technology has an impact on the visibility of their businesses in an increasingly competitive market. Google Maps is one platform that can be used to effectively increase the reach of business information and promotion, but its use is still not optimal among MSME players. This community service activity aims to improve digital navigation literacy through training on the use of Google Maps for MSMEs in Banyubiru Village. The implementation methods include socialization, technical training on creating and managing business profiles on Google Maps, direct mentoring, and evaluation of platform utilization. The activity was attended by 30 SME operators with diverse business backgrounds. The results showed an increase in participants' skills in creating business profiles, uploading product photos, updating information, and responding to customer reviews. Post-activity evaluations showed an increase in the online reach of business information, as indicated by an increase in the number of searches and visits to business locations. In conclusion, digital navigation literacy based on Google Maps can be an effective strategy to support promotion and expand the market for SMEs in rural areas.